Circadian regulator REV-ERBα is a master regulator of tumor lineage plasticity and an effective therapeutic target - Xiong Zhang; Yatian Yang; Hongye Zou; Demin Cai; Eva Corey; Amina Zoubeidi; Su Hao Lo; Ai-Ming Yu; Ronald M. Evans; Hong-Wu Chen (Proceedings of the National Academy of Sciences, 2025)
Epigenetic and transcriptional dysregulation plays a fundamental role in tumor lineage plasticity (LP). However, the underlying mechanisms, especially for the initial events of LP development, are still poorly understood. Here, we report that in progression of prostate cancer from adenocarcinoma to treatment-induced neuroendocrine prostate cancer (t-NEPC), anti-androgen receptor (AR) signaling inhibitors (ARSIs) reprogram the function of circadian regulator/nuclear receptor REV-ERBα by switching its target gene programs from kinase signaling and metabolic programs to programs of LP, which includes neurogenesis, stem cell, and epithelial–mesenchymal transition as well as over fifteen LP drivers including POU3F2/BRN2, ASCL1, FOXA2, ONECUT2, and MYCN. Unexpectedly, REV-ERBα facilitates the chromatin occupancy of BRN2, ASCL1, and FOXA1 in their activation of LP programs, thus functioning as a master regulator of ARSI-induced LP driver network. Mechanistically, REV-ERBα induces chromatin accessibility and H3K27ac modification at promoters of LP genes through its recruitment of BRD4 and p300. Overexpression of REV-ERBα alone is sufficient to induce LP and neuroendocrine phenotype and confers resistance to ARSI in adenocarcinoma cells. Loss of REV-ERBα potently inhibits NEPC cell growth and abolishes the expression of LP drivers and gene programs. Pharmacological inhibition of REV-ERBα exhibits high potency in blocking the growth of NEPC tumors including patient-derived xenografts. Our findings reveal that therapy-induced LP development entails a coordinated induction of a network of LP drivers and that REV-ERBα is an unexpected master regulator of the network and a promising therapeutic target for treatment of advanced prostate cancer such as NEPC.